Burden of viral gastroenteritis in children living in rural China: Population-based surveillance. (January 2020) - Wang, Jin-Xia; Zhou, Hong-Lu; Mo, Zhao-Jun; Wang, Song-Mei; Hao, Zhi-Yong; Li, Yue; Zhen, Shan-Shan; Zhang, Can-Jing; Zhang, Xin-Jiang; Ma, Jing-Chen; Qiu, Chao; Zhao, Gan; et al.
Highlights: Rotavirus vaccine has not been introduced into the national immunization program and norovirus vaccines are being developed without a comprehensive understanding of epidemiology in China. Population-based diarrhea surveillance was conducted in children <5 years of age in the rural north and south of China. Rotavirus and norovirus are the two most important viral pathogens causing childhood diarrhea in rural China. Vaccines to protect against rotavirus and norovirus are desirable for prevention of childhood diarrhea in China. Abstract: Background: Despite the considerable disease burden caused by the disease, rotavirus vaccine has not been introduced into routine national immunization schedule, and norovirus vaccines are being developed without a comprehensive understanding of gastroenteritis epidemiology. To bridge this knowledge gap, we investigated the disease burden of viral gastroenteritis in rural China. Methods: Between October 2011 and December 2013, population-based surveillance was conducted in Zhengding and Sanjiang counties in China. Stool samples were collected from children <5 years of age with diarrhea. All specimens were tested for rotaviruses, noroviruses, sapoviruses, enteric adenoviruses, and astroviruses. Results: The most common pathogen causing diarrhea was rotavirus (54.7 vs 45.6 cases/1, 000 children/year in Zhengding and Sanjiang, respectively), followed by norovirus (28.4 vs 19.3 cases/1, 000 children/year in Zhengding and Sanjiang, respectively). The highest incidence of these viruses was observed in children 6–18 months of age. Among the 5 viral pathogens, rotaviruses caused the most severe illness, followed by noroviruses. Conclusion: Rotavirus and norovirus are the 2 most important viral pathogens causing childhood diarrhea in both northern and southern China; they should be the major targets for viral gastroenteritis prevention strategies among children in China.